Mediocre : [compact disc, unabridged] the dangerous legacy of white male America - Oluo, Ijeoma (Hachette Book Group, 2020)
Ijeoma Oluo investigates the real costs and the subversive history of white male American identity in order to find a way it can be reimagined, one free from racism, sexism, and oppression.